Implementasi Pendidikan Agama Islam Untuk Lansia Di Panti Sosial Tresna Wherda Provinsi Bengkulu - Arci Novita Dahyani; Zulkarnaen S; Nely Marhayati (Institut Agama Islam Negeri Bengkulu, 2020)
Law Number 13 of 1998 concerning elderly welfare chapter 5 article 13 which reads: (1) Religious and mental spiritual service for the elderly is intended to strengthen the sense of desire and devotion to God Almighty. (2) Religious and mental spiritual services as referred to in paragraph (1) are carried out through increased religious activities in accordance with their respective religions and beliefs. Elderly education is one form of non-formal education. Islamic religious education in non-formal institutions is affirmed in Law Number 20 of 2003 concerning the National Education System, Article 30 which reads: (1) Religious education is carried out by the government and / or community groups and religious adherents, in accordance with statutory regulations . (2) Religious education functions to prepare students to become members of the community who understand and practice the values of their religious teachings and / or become religious scholars. (3) Religious education can be carried out in formal, non-formal and informal education channels. Based on observations obtained by researchers at Tresna Wherda Social Institution in Bengkulu Province, there are 82 elderly people with details, 52 men and 30 women. The purpose of this study is to describe the Implementation of Islamic Education for the elderly in Tresna Wherda Social Institution in Bengkulu Province and describe the Supporting Factors and Inhibiting Factors of Islamic Religious Education for the elderly in Tresna Wherda Social Institution in Bengkulu Province. This type of research is a qualitative study using a phenomenological approach. The results of this study are: 1) The implementation of Islamic religious education for the elderly at Tresna Wherda Social Institution in Bengkulu Province, among others: religious lectures (recitation), Fostering Worship (Congregational Prayer) which is carried out five times a day namely dawn, dhuhur, ashar, maghrib, and isya ', and Development of Reading and Memorization of Short Letters in juz 30. 2) Factors that influence Islamic religious education for the elderly at Tresna Wherda Social Institution in Bengkulu Province are: Supporting factors in the form of religious builders (religious teachers and religious teachers) qualified, a conducive environment, adequate facilities for the elderly, and high interest and motivation of the elderly in attending Islamic religious education. Inhibiting factors in the form: decreased physical condition of the elderly and diverse backgrounds of the elderly.